APPLICATION OF WELL LOG ANALYSIS IN ASSESSMENT OF PETROPHYSICAL PARAMETERS AND RESERVOIR CHARACTERIZATION OF WELLS IN THE “OTH” FIELD, ANAMBRA BASIN, SOUTHERN NIGERIA - Eugene URORO; Efe Lucky IGHARO (International Journal of Science and Engineering, 2015)
Over the past years, the Anambra basin one of Nigeria’s inland basins has recorded significant level of hydrocarbon exploration activities. The basin has been confirmed by several authors from source rock analyses to have the potential for generating hydrocarbon. For the hydrocarbon to be exploited, it is imperative to have a thorough understanding of the reservoir. Computer-assisted log analyses were employed to effectively evaluate the petrophysical parameters such as the shale volume (Vsh), total porosity (TP), effective porosity (EP), water saturation (Sw), and hydrocarbon saturation (Sh). Cross-plots of the petrophysical parameters versus depth were illustrated. Five hydrocarbon bearing reservoirs were delineated in well 1, four in well 2. The reservoirs in well 3 do not contain hydrocarbon. The estimated reservoir porosity varies from 10% to 21% while their permeability values range from 20md to 1400md. The porosity and permeability values suggest that reservoirs are good enough to store and also permit free flow of fluid. The volume of shale (0.05% to 0.35%) analysis reveals that the reservoirs range from shaly sand to slightly shaly sand to clean sand reservoir. On the basis of petrophysics data, the reservoirs are interpreted a good quality reservoir rocks which has been confirmed with high effective porosity range between 20% and high hydrocarbon saturation exceeding 55% water saturation in well 1 and well 2. Water saturation 3 is nearly 100% although the reservoir properties are good.